Correlation between sarcopenia and cirrhosis: a meta-analysis - Cui, Yifan; Zhang, Mingming; Guo, Jing; Jin, Jin; Wang, Haijiao; Wang, Xinran (Frontiers in Nutrition, 2024)
Background The relationship between sarcopenia and cirrhosis is unclear. In this research, our aim is to evaluate the prevalence of sarcopenia among individuals with liver cirrhosis and its correlation with survival and mortality risks. Methods We conducted searches on PubMed, Web of Science, EMBASE, and Cochrane for English articles published up to July 10, 2023, and additionally manually searched the bibliography of relevant articles. We incorporated research on sarcopenia in patients with cirrhosis to examine the connection between sarcopenia and the likelihood of survival and mortality. Statistical analyses were carried out utilizing the Stata version 15.1 software. Depending on the heterogeneity of the results, we employed either fixed-effects models or random-effects models for data synthesis. To assess publication bias, we employed funnel plots and conducted Egger’s test. Results We included 40 studies involving 8,945 patients with cirrhosis. The overall prevalence of cirrhosis was 41% (95% CI 34%–48%). Male patients and those with liver cirrhosis and hepatic encephalopathy had a higher prevalence of sarcopenia (44% for male patients and 48% for hepatic encephalopathy patients). Sarcopenia emerged as a risk factor for both survival (HR = 2.57, 95% CI 2.02–3.27, p < 0.001) and mortality (HR = 2.13, 95% CI 1.86–2.44, p < 0.001) in patients with cirrhosis. Subgroup analyses consistently yielded the same results for study sites, whether HCC patients were excluded from the cohort, whether patients were from the liver transplant cohort or had undergone tips surgery, the definition of sarcopenia (L3-SMI or other methods), and the diagnostic criteria used by patients. The presence of sarcopenia was also a significant risk factor for hepatic encephalopathy [HR = 2.27, 95% CI (1.76–2.94), p < 0.001]. Conclusion This systematic review and meta-analysis reveal that patients with cirrhosis have a prevalence of sarcopenia of 41% and is associated with survival rate and mortality rate. Therefore, we should attach importance to the screening of sarcopenia in patients with cirrhosis, early detection of susceptible populations, and appropriate measures to reduce the occurrence and adverse outcomes. Systematic review registration:https://www.crd.york.ac.uk/PROSPERO/#recordDetails.